“Can I Make a Party, Mum?” The Development of Requests from Childhood to Adolescence - Barón Parés, Júlia (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2015)
This study presents how requests are acquired and developed over an eight-year period by an EFL learner in a foreign language setting, where target language pragmatics is not an issue dealt with in the classroom. In order to assess pragmatic development, a role-play requiring requests was used. This study has been triggered by the fact that longitudinal studies have commonly been considered very valuable, since development of the same participants can be traced over a long period of time. The development of requests has been followed by, first, examining what types of requests were produced by the learner at the different stages of pragmatic development; second, by analyzing the use of request modification; and, finally, by placing the learner’s requests at different stages of development. The results seem to show that little development can be traced at very early stages of acquisition, and that it is not until Grade 11 that a development toward more pragmatically appropriate productions can be found. Keywords: interlanguage pragmatics; requests; pragmatic development; longitudinal study; EFL